2011
DOI: 10.5505/1304.8503.2011.92486
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve in laparoscopic renal surgery and influencing factors

Abstract: Son 20 yıl içerisinde edinilen deneyimler böbrek cerrahisinde laparoskopik girişimlerin, kabul edilebilir cerrahi sonuçlar, düşük komplikasyon oranları ve yüksek hasta memnuniyeti ve yaşam kalitesi ile açık cerrahi prosedürlere alternatif olduğunu göstermektedir. Ancak, laparoskopik cerrahinin, açık cerrahiye oranla daha teknik bir prosedür olması ve öğrenim sürecinin nispeten uzun olması prosedürü zorlaştırmaktadır. Bu çalışmadaki amacımız, laparoskopik böbrek ameliyatlarındaki öğrenim sürecini irdeleyerek, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For instance, these influential factors include postinflammatory processes as xanthogranulomatous pyelonephritis, and renal tuberculosis, increased complication risk secondary to perinephric adhesions, and risk of conversion to open surgery. [12,15] In their series of simple LNs, Toktaş et al [16] reported higher complication rates in renal dysfunctions caused by stone disease, and in nephrectomies performed to treat inflammatory conditions. Study of Soulie et al [17] also supports the outcomes of Toktaş et al [16] In our study we examined the effect of atrophic or hydronephrotic kidneys developed independent of the etiology of nonfunctional kidney on the outcomes of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, these influential factors include postinflammatory processes as xanthogranulomatous pyelonephritis, and renal tuberculosis, increased complication risk secondary to perinephric adhesions, and risk of conversion to open surgery. [12,15] In their series of simple LNs, Toktaş et al [16] reported higher complication rates in renal dysfunctions caused by stone disease, and in nephrectomies performed to treat inflammatory conditions. Study of Soulie et al [17] also supports the outcomes of Toktaş et al [16] In our study we examined the effect of atrophic or hydronephrotic kidneys developed independent of the etiology of nonfunctional kidney on the outcomes of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…[12,15] In their series of simple LNs, Toktaş et al [16] reported higher complication rates in renal dysfunctions caused by stone disease, and in nephrectomies performed to treat inflammatory conditions. Study of Soulie et al [17] also supports the outcomes of Toktaş et al [16] In our study we examined the effect of atrophic or hydronephrotic kidneys developed independent of the etiology of nonfunctional kidney on the outcomes of laparoscopy. We observed that operative time was the only statistically significant difference between nephrectomies performed for atrophic or hydronephrotic kidneys.…”
Section: Discussionmentioning
confidence: 99%